Laboratories of authoritarianism - Wang, Yueduan (Stanford journal of international law, 2021)
One of the most commonly cited virtues of American federalism is its "laboratories of democracy " - the notion that decentralization and political competition encourage states to become testing grounds for novel social policies and ideas. This study argues that this concept is not exclusive to federal democracies. Indeed, similar mechanisms can prosper under a regime that is formally unitary and politically authoritarian. By analyzing significant transformations in China, such as marketization and the introduction of competitive elections, this study shows how the party-state systematically utilizes subnational policy experiments to modernize its communist institutions and adapt to the changing political and social landscape. Like in the United States, experiments in China result from the interaction between its constitutional structure and competition among political elites. However, contrary to the United States, China's center-local constitutional relationship is characterized by a unique combination of decentralized policymaking powers and centralized appointment/removal powers. It is under this arrangement that various Party factions compete for political supremacy. Amid such competition, faction members in subnational leadership positions use their broad policy discretion to pilot new ideas that conform to the faction's policy objectives. Such innovation often spread either by peer-to-peer learning or through national adoption pushed for by the faction's central leadership. This cycle of experimentation has become a frequently utilized method for political elites to expand their policy and political influence and is responsible for many institutional innovations critical to the communist country's modernization and eventual rise as a global superpower. However, the top-down nature of China's center-local structure means that its "laboratories of authoritarianism" are subject to the vicissitudes of factional politics in the center, making them less stable than their democratic counterparts.